Rare case of low-grade extranodal NK/T-cell lymphoma, nasal type, arising in the setting of chronic rhinosinusitis and harboring a novel N-terminal KIT mutation - Kyle Devins; Stephen J. Schuster; Gabriel C. Caponetti; Agata M. Bogusz (BMC, 2018)
Abstract Background Extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT), is a rare aggressive subtype of non-Hodgkin lymphoma characterized by angioinvasion, angiodestruction, necrosis and strong association with Epstein-Barr virus (EBV). ENKTCL-NT occurs worldwide and is more prevalent in Asian and the Native American populations of Mexico, Central and South America. It represents approximately 10% of all peripheral T-cell lymphomas worldwide. The aim of this report is to present a rare case of ENKTCL-NT with an unusually indolent clinical course and low-grade histopathologic features. Case presentation A 71-year-old Asian woman with a long-standing history of seasonal rhinosinusitis presented with persistent nasal congestion, cough, and fever unresponsive to antihistamines and antibiotics. Histopathological evaluation of a polypoid nasal mass revealed an atypical infiltrate with predominantly small lymphoid cells that were CD2+, surface CD3-, cytoplasmic CD3+, CD5(dim)+, CD7(dim)+, cytotoxic markers (granzyme B and perforin)+, EBER+ and CD56-. The Ki-67 proliferative index was very low (< 1%). T-cell receptor gamma gene rearrangement studies were positive for a monoclonal rearrangement, and sequencing studies identified a novel KIT mutation (p. K167 M, c. 500 A > T). A diagnosis of low-grade ENKTCL-NT was rendered. Conclusions Our case of ENKTCL-NT is unusual due to (1) an indolent clinical course (2) low-grade histopathologic features including a low proliferative index (3) lack of CD56 expression and (4) a novel KIT mutation. This case raises awareness of the existence of a subset of cases of ENKTCL-NT that can potentially be misdiagnosed as a reactive process, particularly in patients with recurrent chronic rhinosinusitis.